1979
DOI: 10.1111/j.1432-1033.1979.tb13178.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Methylation of Cytoplasmic Ribosomal RNA from Cultured Higher Plant Cells

Abstract: The methylation of cytoplasmic ribosomal RNA of cultured sycamore cells (Acer pseudoplatanus L.) was investigated. Labelled 17-S and 26-S rRNA were prepared from cells that had been incubated with either [32P]phosphate, methionine. Ion-exchange resin chromatography of 0.3 M KOH or 1 M HCl hydrolysates and two-dimensional chromatographic analyses of phosphodiesterase plus phosphatase digests of 17-S and 26-S rRNA were performed.17-S and 26-S rRNA contain 49 and 91 methyl groups per molecule, respectively. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Thus methylation at Am2116 could either implicate another unidentified snoRNA or, alternatively, U60.1f/.2f could methylate both Gm2114 and Am2116. No other modified nucleotides have been mapped except for the three reported here, but early biochemical studies indicate that neighbouring 2'-O-methylated residues do occur in plant rRNAs (29).…”
Section: Evolutionary Conservation Of Snorna-directed Rrna Methylatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus methylation at Am2116 could either implicate another unidentified snoRNA or, alternatively, U60.1f/.2f could methylate both Gm2114 and Am2116. No other modified nucleotides have been mapped except for the three reported here, but early biochemical studies indicate that neighbouring 2'-O-methylated residues do occur in plant rRNAs (29).…”
Section: Evolutionary Conservation Of Snorna-directed Rrna Methylatiomentioning
confidence: 99%
“…These include U3, U14 and seven other box C/D and one box H/ACA snoRNAs described in Arabidopsis or maize (28). Many other snoRNAs should exist in plants since early biochemical studies indicate the presence of numerous modified nucleotides in plant rRNAs (29), but these have never by guest on May 7, 2018 http://www.jbc.org/ Downloaded from been mapped. In addition, many Arabidopsis genomic sequences displaying box C/D or H/ACA snoRNA features can be find in the databanks.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, early biochemical data revealed that rRNAs are highly modified implicating overall 120 2′‐ O ‐ribose methylated residues (Lau et al ., 1974; Cecchini and Miassod, 1979). The mechanisms guiding rRNA methylation depending on fibrillarin and C/D snoRNAs are conserved in plants (Barneche et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies revealed more than 120 2 0 -O-ribose methylation sites in the rRNAs of sycamore plant cell (23). Compared with other eukaryotic species, plants contain a number of 2 0 -O-ribose methylation sites in rRNAs (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, numerous novel snoRNA homologues have been identified from various eukaryotes including vertebrate, invertebrates, yeast and protests, and even from archael organisms (15 -22). Early studies revealed more than 120 2 0 -O-ribose methylation sites in the rRNAs of sycamore plant cell (23). Compared with other eukaryotic species, plants contain a number of 2 0 -O-ribose methylation sites in rRNAs (24,25).…”
Section: Introductionmentioning
confidence: 99%